Implementation of Early Intervention with Family Resourced to Improve Development of Expressive Language in Children with Cerebral Palsy - Hipni Mubarok Abidin; Endang Rochyadi; Neng Tria Sutriani (Indonesian Journal of Community and Special Needs Education, 2021)
The purpose of this study was to determine the implementation of early intervention with family resources to improve expressive language development in children with cerebral palsy. Early intervention with family resources is carried out on children with cerebral palsy who have problems in the development of their expressive language, so the communication method used is augmentation using alternative and augmentative communication tools called ASIK (I'm Ready to Communicate). This research method uses experiments, starting from modelling, transfer by parents, so that parents can independently intervene with their children. The results showed that children can express their desires by showing pictures that are in accordance with the wishes of their parents, so that parents can understand what their children want. Based on these results, the implementation of early intervention with family resources using ASIK communication tools can improve the development of expressive language in children with cerebral palsy.